2012
DOI: 10.1371/journal.pone.0043273
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Kinetic Model for Assemblies of Amyloid Fibrils and Its Application to Polyglutamine Aggregation

Abstract: Protein polymerization consists in the aggregation of single monomers into polymers that may fragment. Fibrils assembly is a key process in amyloid diseases. Up to now, protein aggregation was commonly mathematically simulated by a polymer size-structured ordinary differential equations (ODE) system, which is infinite by definition and therefore leads to high computational costs. Moreover, this Ordinary Differential Equation-based modeling approach implies biological assumptions that may be difficult to justif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(97 citation statements)
references
References 28 publications
0
94
0
Order By: Relevance
“…They tend to assemble as toxic fibrillar structures, which may in turn associate into mature amyloid inclusions. Several mathematical models have been proposed to explain the protein aggregation process in ND: Stochastic nucleation and fibril dynamics, for instance, have been modelled using a two‐step reaction mechanism 42, 43, 44, 45, 46, 47 and validated with empirical data 48.A micelle intermediate on the pathway of protein aggregation has been described using mathematical models 49, 50.Furthermore, models of inhibiting end‐blocking drugs have also been formulated for describing the protein aggregation process 51, 52, 53. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They tend to assemble as toxic fibrillar structures, which may in turn associate into mature amyloid inclusions. Several mathematical models have been proposed to explain the protein aggregation process in ND: Stochastic nucleation and fibril dynamics, for instance, have been modelled using a two‐step reaction mechanism 42, 43, 44, 45, 46, 47 and validated with empirical data 48.A micelle intermediate on the pathway of protein aggregation has been described using mathematical models 49, 50.Furthermore, models of inhibiting end‐blocking drugs have also been formulated for describing the protein aggregation process 51, 52, 53. …”
Section: Resultsmentioning
confidence: 99%
“…A micelle intermediate on the pathway of protein aggregation has been described using mathematical models 49, 50.…”
Section: Resultsmentioning
confidence: 99%
“…As a conclusion, the final size distribution may have the same shape for protein polymerization that involves a nucleation as for synthetic polymerization of living polymers that starts by an initiation, but the kinetics induced by a nucleation may strongly differ from the one induced by an initiation. However in the cases of protein polymerization that are quickly activated, i.e., where nucleation does not exist (nucleus size considered as equal to 1) or is not a rate-limiting step [39], the kinetics might be similar to that of synthetic living polymers.…”
Section: Discussionmentioning
confidence: 99%
“…T V for δ small -5 to 10% -represents an alternative definition for the lag-time of the reaction [17].…”
Section: B Asymptotics Of the Time For δ Reaction Completionmentioning
confidence: 99%
“…Such a simplification is also justified by the fact that current kinetics measurements of amyloid growth exhibit variability on the timecourse of the total polymerised mass, without giving any information on the size distribution of fibrils. Previous studies (see for instance [17], Supplemental material (S.M.) 2) have shown that the detail of the reactions of secondary pathways, such as a fragmentation kernel, may have a major impact on the size distribution of polymers, but comparably smaller effects on the timecourse of the polymerised mass.…”
Section: A Phenomenological Stochastic Modelmentioning
confidence: 99%